Black Hammer. Volume 6, Reborn. Part II - Lemire, Jeff (Lemire, Jeff. Black hammer, 2022)
"A multidimensional nightmare unfolds and wreaks havoc on Spiral City as the powerful superhero known as the Black Hammer joins forces with the brutal vigilante known as the Skulldigger to put an end to this madness. Black Hammer: Reborn is the next era of the Black Hammer Universe; a twelve-issue series by Jeff Lemire, Caitlin Yarsky, Malachi Ward and Matthew Sheean that juxtaposes an achingly human story of domestic life, marriage, parenthood, and destiny with a pulse-pounding superhero thriller that peels back new layers of mystery, and pulls the Black Hammer history into the present."--